Tax Fairness and Tax Compliance in Iraq - Juhi, Ahmed Hamid (2011)
This study carries out a research on tax fairness and tax compliance in Iraq. Non random sampling method has been applied to select the respondents. The respondents are government servants, who are full time employee and they are registered tax payers. The study investigates the correlation of tax compliance and tax fairness. Demographic backgrounds of respondents are also measured in correlation with tax fairness and tax compliance. The study is limited to government servants in Iraq with certain demographic attributes like income level, level of education, gender, age and years of working experience. The purpose of the study is to examine whether there is correlation between tax fairness and tax compliance, moreover correlating demographic attribute to tax compliance. The result of the study has indicated that tax compliance and tax fairness has positive correlation. It shows that the correlation between tax fairness and tax compliance has been affected by the level of experience as tax payers. Demographic attributes has shown impact on tax compliance.